2019
DOI: 10.1001/jamadermatol.2019.0629
|View full text |Cite
|
Sign up to set email alerts
|

All-Cause and Cause-Specific Mortality Risks Associated With Alopecia Areata

Abstract: IMPORTANCE Alopecia areata is associated with diverse systemic and psychiatric diseases. However, whether all-cause and cause-specific mortality in patients with alopecia areata differs from that of the general population remains unclear. OBJECTIVE To investigate all-cause and cause-specific mortality risk in patients with alopecia areata. DESIGN, SETTING, AND PARTICIPANTS Using the National Health Insurance Service database and National Death Registry of Korea, a retrospective cohort study of participants ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…In a Korean study, 209 of the 220 patients with an ICD 10 code of L63 who had their chart reviewed were confirmed to have AA, resulting in a PPV of 95.0%. [ 5 ] The criteria used to validate the charts was not described. Overall, our PPVs lie within the range of those published by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean study, 209 of the 220 patients with an ICD 10 code of L63 who had their chart reviewed were confirmed to have AA, resulting in a PPV of 95.0%. [ 5 ] The criteria used to validate the charts was not described. Overall, our PPVs lie within the range of those published by previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Huang et al found that AA was not related to an increased risk of acute myocardial infarction without statistical significance [ 8 ]. In addition, Lee et al showed the risk of cardiovascular mortality is not associated with presence of AA [ 26 ]. However, Shin et al claimed significantly increased risk of acute myocardial infarction in patients with AA only in the later stage of the observation [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…If clinicians enter the wrong diagnosis, the claim is refused according to the Health Insurance Review and Assessment Service's assessment evaluation [13]. Thus, it is assumed that the entered diagnostic code is reliable and extensive research has been conducted on this subject in Korea [14,15].…”
Section: Data Sourcesmentioning
confidence: 99%